Penerapan Teknologi Augmented Reality dan Virtual Reality dalam Peningkatan Pembelajaran Siswa Sekolah Dasar - Randy Permana; Eka Praja Wiyata Mandala; Dewi Eka Putri; Musli Yanto (Universitas Putra Indonesia YPTK Padang, 2022)
The need for digital technology has increased along with the development of new technological discoveries. These needs cause changes in the pattern of human life in socializing, doing activities, as well as in understanding and learning things. One technology that continues to experience development is mobile technology, where this technology is owned by the majority of the earth's population. The application of mobile technology in the learning process is one of the choices at this time, where practicality and mobile are one of the strong reasons for using this technology. In this service, Augmented Reality and Virtual Reality technology will be introduced to support the learning process. AR and VR technologies introduced include digital content that enters the realm of education, where using AR content can help accelerate and improve the student learning process.